PHARMACOECONOMIC ANALYSIS OF OLMESARTAN THERAPY IN THE INDIVIDUAL–LEVEL MANAGEMENT OF ARTERIAL HYPERTENSION - S. G. Gorokhova; V. V. Ryazhenov (Российский кардиологический журнал, 2012)
The pharmacoeconomic analysis compared the strategies of arterial hypertension (AH) management using different angiotensin II receptor blockers (ARB). The first stage of the analysis included the cost-effectiveness modelling in patients with moderate AH receiving olmesartan, losartan, or valsartan. As the second stage, a similar analysis was performed for patients with moderate AH and diabetes mellitus (DM) or renal failure. Clinical and economic benefits were demonstrated for olmesartan, compared to losartan or valsartan. The cost-effectiveness ratio was minimal for olmesartan therapy in patients with both moderate AH and a combination of moderate AH and DM or renal failure. Therefore, olmesartan should be considered as a first-choice medication while selecting the optimal clinical and pharmacoeconomic strategy of AH management with ARB.